Magnetic force microscopy of atherosclerotic plaque - Alexeeva T.A.; Gorobets S.V.; Gorobets O.Yu.; Demianenko I.V.; Lazarenko O.M. (Medičnì Perspektivi)
In this work by methods of scanning probe microscopy, namely by atomic force microscopy and magnetic force microscopy the fragments of atherosclerotic plaque section of different nature were investigated. The fragments of atherosclerotic vessels with elements of immature plaque were taken during the coiled artery bypass surgery by alloprosthesis. As the result of investigation we found magnetically ordered phase of endogenous origin in the fragment of solid plaque of mixed structure. This phase is presents biogenic magnetic nanoparticles and their clusters with average size characteristic of 200-400 nm.